Estimation and Evaluation of New Features from Phonocardiogram for Detecting Cardiovascular Abnormalities - Mahdi Nourian-Zavareh; Saeed Kermani; Mohammad Hashemi-Jazi; Maryam Samieinasab (مجله دانشکده پزشکی اصفهان, 2019)
Background: In the world, cardiovascular diseases are the major cause of death, as 31% of global mortality is from them. Due to problems such as the lack of technologies such as echocardiography, and limited access to cardiologists in deprived areas, automatic methods for detecting heart abnormalities in phonocardiogram (PCG) are used.